Féminisme, anarchisme et fédéralisme. L'exemple de l'organisation Alternative libertaire entre 2006 et 2012. (2nd April 2016) - Pereira, Irène
Abstract: This article examines the spatial, and especially scalar, dimension of feminism in a contemporary French anarchist organisation. This perspective is contextualised by a reminder of the role of feminism in the political history of anarchism and of the role of the spatial dimention through the question of anarchist federalism. The empirical study is based on research conducted through participant observation within the organisation Alternative Libertaire between 2006 and 2012. The problem to be addressed is the question of whether anarchist women succeed as well as they claim in bringing into question, in their promotion of feminism both inside the organisation and outside, the centrality of Paris in favour of an anarchist federalism. For this reason two scales or levels are studied: the national level and the local level of the city. The city of Paris is treated as both the national capital and as a locality.